2024
DOI: 10.3390/cancers16040751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liquid-Based Preparations with Conventional Smears in Thyroid Fine-Needle Aspirates: A Systematic Review and Meta-Analysis

Yun Jin Kang,
Hyeon Woo Lee,
Gulnaz Stybayeva
et al.

Abstract: Background: To compare conventional smears (CSs) and liquid-based preparations (LBPs) for diagnosing thyroid malignant or suspicious lesions. Methods: Studies in the PubMed, SCOPUS, Embase, Web of Science, and Cochrane database published up to December 2023. We reviewed 17 studies, including 15,861 samples. Results: The diagnostic odds ratio (DOR) for CS was 23.6674. The area under the summary receiver operating characteristic curve (AUC) was 0.879, with sensitivity, specificity, negative predictive value, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Some previous studies concluded that liquid-based cytology serves as a useful adjunct diagnostic method, and its combination with conventional smears has been shown to reduce unnecessary thyroidectomies due to the good identification of malignant and suspicious thyroid lesions [28,29]. However, a recently published meta-analysis study by Kang et al in 2024 [30] concluded that the diagnostic accuracy of FNAC in thyroid nodules did not significantly differ among conventional and/or liquid-based cytology, but comparing two kits (ThinPrep and SurePath) revealed a significant difference, suggesting that SurePath kits might be more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies concluded that liquid-based cytology serves as a useful adjunct diagnostic method, and its combination with conventional smears has been shown to reduce unnecessary thyroidectomies due to the good identification of malignant and suspicious thyroid lesions [28,29]. However, a recently published meta-analysis study by Kang et al in 2024 [30] concluded that the diagnostic accuracy of FNAC in thyroid nodules did not significantly differ among conventional and/or liquid-based cytology, but comparing two kits (ThinPrep and SurePath) revealed a significant difference, suggesting that SurePath kits might be more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent cancer in the endocrine system is thyroid cancer ( 1 ), among which papillary thyroid carcinoma (PTC) remains the most common type, accounting for 84% of all malignancies ( 2 ). The main clinical challenge is to rule out malignancy as most thyroid nodules are asymptomatic, benign, and do not require surgical treatment.…”
Section: Introductionmentioning
confidence: 99%